Effective performance of ilmenite oxygen carrier for chemical looping combustion of carbon monoxide, hydrogen, and methane in a fluidized bed reactor. (15th December 2022) - Narindri Rara Winayu, Birgitta; Li, Chun-Ta; Chu, Hsin
Abstract: Extremely high human activities using fossil fuel burning process that leads to the need of urgent implementation of carbon capture utilization and storage (CCUS). Chemical looping combustion (CLC) is considered a competent strategy for cost effective CCUS due to the improvement in combustion efficiency and emission reduction of nitrogen oxides (NOx). Ilmenite ore is a potential material to be applied as an oxygen carrier (OC) for Chemical Looping Combustion (CLC). In this study, calcined ilmenite under 1000 °C was applied as the oxygen carrier to react with coal or biomass gasified syngas which is composed of H2, CO, and CH4 in a fluidized bed reactor. Various operating parameters were tested along with the oxygen carrier property analysis, kinetics study, and reaction mechanism prediction. The results showed that the calcined ilmenite performed 88.7, 64.2, and 79.2% conversion of H2, CO, CH4, respectively. In the fluidized bed reactor, increasing syngas concentration, operating temperature, and superficial velocity caused higher reaction rate and oxygen carrier utilization. Application of 25% CO + 15% H2 as complex syngas achieved the highest oxygen carrier utilization. However, the implementation of CO and CH4 led to the carbon deposition and further blocking the surface of oxygen carrier. Moreover, the application of oxygen carrier in a higher redox cycle resulted the reduction of its performance due to the sintering and poor surface properties. Graphical abstract: Image 1 Highlights: Calcined ilmenite presented efficient performance as an oxygen carrier. Calcined ilmenite converted 88.7, 64.2, 79.2% of H2, CO, and CH4, respectively. High syngas concentration or superficial velocity lift reaction rate and utilization. Higher redox cycle test accumulated carbon deposition and resulted in masking.